Growth and Dryma Tter Production in Groundnut-Pigeonpea Intercropping System - Reddy, P R; Sekhar, A Chandra; Reddy, Y Rama (Annals of Arid Zone, 2016)
In an experiment conducted at Agricultural Research Station, Anantapur to study the effect of intercropping on the growth and yield of component crops of groundnut and pigeonpea during 1986 and 1987 kharif seasons, growth and drymatter production of component crops were also studied. A favourable early monsoon during 1986 helped in better vegetative growth of both the crops compared to 1987. LAI in pigeonpea increased gradually upto 120 to 150 days after sowing (DAS) and than declined in June sown crop. where as LAI increased upto 90 day only in the August sown crop. However, drymatler production increased gradually upto harvest. June sown pigeonpea recorded significantly more LAI and drymatter than August sown crop, leading to higher grain yield. Sole pigeonpea recorded significantly more LAI than intercrop. Sole groundnut recorded significantly more LAY and drymatter at all the . stages of crop growth, leading to higher pod yields. LAY in groundnut increased upto 60 DAS and then declined. Drymatter production increased upto harvest in 1987, but only upto 60 daysÂ· in 1986. LAY and drymatter production in the staggered ground nut was very low because of competition from pigeonpea for available resources which decreased the pod yield to a great extent.